Double-sided adhesive tape

By using double-sided adhesive tape with a specific composition and structure, the problems of easy breakage and poor reworkability of existing stretchable double-sided adhesive tapes during peeling are solved, achieving high initial adhesion, good elongation and smooth removal.

CN114729236BActive Publication Date: 2025-01-07NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080076968.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-30
Filing Date
2020-09-14
Publication Date
2025-01-07
Estimated Expiration
2040-09-14

AI Technical Summary

Technical Problem

Existing stretchable double-sided adhesive tapes are prone to breakage when peeled off from the substrate, have poor reworkability, and are difficult to remove smoothly.

Method used

The double-sided adhesive tape, which contains both acrylic and rubber adhesives, is used. The substrate layer uses polyolefin, thermoplastic polyurethane, or styrene polymers to ensure that the initial adhesion and elongation at break meet specific standards. It is designed as a three-layer structure to improve elongation and pull-out properties.

Benefits of technology

It achieves excellent initial adhesion to the substrate, can stretch fully without breaking easily, can be easily pulled off the substrate, and has excellent reworkability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114729236B_ABST
    Figure CN114729236B_ABST
Patent Text Reader

Abstract

The present invention provides a double-sided adhesive tape which has excellent initial adhesion to an adherend, can be sufficiently stretched, is not easily broken even when sufficiently stretched, can be smoothly pulled off from the adherend in a stretched state, and has excellent reworkability. A double-sided adhesive tape in an embodiment of the present invention comprises an adhesive layer (B1), a substrate layer (A) and an adhesive layer (B2) in this order, wherein the adhesive layer (B1) and the adhesive layer (B2) each contain at least one selected from the group consisting of an acrylic adhesive and a rubber adhesive, and the acrylic adhesive contains a filler, the substrate layer (A) contains at least one selected from the group consisting of a polyolefin, a thermoplastic polyurethane and a styrene polymer as a resin component, the adhesive layer (B1) and the adhesive layer (B2) each have an initial adhesive force of 5 N / 10 mm or more, the initial adhesive force being the initial adhesive force to a SUS plate under the conditions of a peel angle of 180 degrees and a peel speed of 300 mm / min under an environment of 23° C. and 50% RH specified in JIS-Z-0237-2000, and the double-sided adhesive tape has an elongation at break of 600% or more as measured by the “elongation” measurement method specified in JIS-K-7311-1995.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a double-sided adhesive tape. Background Art

[0002] Double-sided pressure-sensitive adhesive tapes are used to fix or temporarily fix parts of electronic devices, typically mobile devices such as mobile phones, smartphones, and tablet terminals.

[0003] Double-sided pressure-sensitive adhesive tapes are required to exhibit pressure-sensitive adhesive strength above a predetermined level in order to prevent adhesion failures such as peeling and displacement from occurring during use.

[0004] On the other hand, for double-sided adhesive tape, sometimes it is removed from the adherend after being pasted on the adherend. For example, sometimes due to a bad situation in the pasting operation of the double-sided adhesive tape, it is necessary to peel off the double-sided adhesive tape and rework. In addition, for example, sometimes in order to repair, replace, inspect, recycle, etc., the member having the adherend pasted with the double-sided adhesive tape, the double-sided adhesive tape must be peeled off.

[0005] When using a double-sided adhesive tape, for example, there is an adherend on at least one side of the double-sided adhesive tape, and representatively, there are adherends on both sides of the double-sided adhesive tape. Therefore, in order to peel off the double-sided adhesive tape from the adherend, when there are adherends on both sides of the double-sided adhesive tape, for example, it is necessary to first peel off one adherend from the other adherend, expose one side of the double-sided adhesive tape, and then peel off the double-sided adhesive tape. In addition, in order to peel off the double-sided adhesive tape from the adherend, when there is an adherend on one side of the double-sided adhesive tape, for example, it is necessary to carefully peel off the double-sided adhesive tape from the adherend.

[0006] However, when the adherend is expensive, there is a high possibility that the adherend will be damaged when the above-mentioned peeling operation or separation operation is performed.

[0007] Therefore, as a method for peeling off a double-sided adhesive tape from an adherend without performing the above-mentioned peeling operation, a scheme using an elongated double-sided adhesive tape has been proposed (for example, Patent Documents 1 to 6). In this method, the following technical concept is adopted: a part of the double-sided adhesive tape attached to the adherend is grasped and pulled, so that the double-sided adhesive tape is stretched and deformed, the adhesive area is reduced, and the double-sided adhesive tape is removed from the adherend in the horizontal direction (shear direction).

[0008] However, conventional stretchable double-sided pressure-sensitive adhesive tapes have problems such as being difficult to remove smoothly due to a large peeling force from an adherend, breaking during removal due to stretching deformation, and poor reworkability.

[0009] Prior art literature

[0010] Patent Literature

[0011] [Patent Document 1] Japanese Patent Application Publication No. 2013-119564

[0012] [Patent Document 2] Japanese Patent Application Publication No. 2016-29155

[0013] [Patent Document 3] Japanese Patent Application Publication No. 2017-197689

[0014] [Patent Document 4] Japanese Patent Application Publication No. 2016-8288

[0015] [Patent Document 5] International Publication No. 2019 / 003933

[0016] [Patent Document 6] Japanese Patent Application Publication No. 2019-6908 Summary of the invention

[0017] Problems to be solved by the invention

[0018] An object of the present invention is to provide a double-sided adhesive tape which has excellent initial adhesion to an adherend, can be sufficiently stretched, is not easily broken even when sufficiently stretched, can be smoothly pulled off from the adherend in a stretched state, and has excellent reworkability.

[0019] Means used to solve problems

[0020] The double-sided adhesive tape in the embodiment of the present invention comprises an adhesive layer (B1), a substrate layer (A), and an adhesive layer (B2) in this order, wherein:

[0021] The adhesive layer (B1) and the adhesive layer (B2) each contain at least one selected from the group consisting of an acrylic adhesive and a rubber adhesive, and the acrylic adhesive contains a filler,

[0022] The substrate layer (A) contains at least one selected from the group consisting of polyolefins, thermoplastic polyurethanes and styrene polymers as a resin component,

[0023] The adhesive layer (B1) and the adhesive layer (B2) each have an initial adhesive force of 5 N / 10 mm or more, the initial adhesive force being the initial adhesive force to a SUS plate under the conditions of 23° C., 50% RH, a peeling angle of 180 degrees, and a peeling speed of 300 mm / min as specified in JIS-Z-0237-2000, and

[0024] The elongation at break of the double-sided adhesive tape measured by the “elongation” measurement method specified in JIS-K-7311-1995 is 600% or more.

[0025] In one embodiment, the tensile strength of the double-sided adhesive tape in the embodiment of the present invention when stretched 600% as measured by the “elongation” measuring method specified in JIS-K-7311-1995 is 12 N / 10 mm or more.

[0026] In one embodiment, the substrate layer (A) is a three-layer substrate layer of two materials having a structure of X layer / Y layer / X layer.

[0027] In one embodiment, the two-material three-layer substrate layer is a two-material three-layer substrate layer having a layer structure of polypropylene / ethylene-vinyl acetate copolymer / polypropylene or a two-material three-layer substrate layer having a layer structure of polyethylene / polypropylene / polyethylene.

[0028] In one embodiment, the total thickness of the double-sided pressure-sensitive adhesive tape in the embodiment of the present invention is 100 μm to 700 μm.

[0029] In one embodiment, the substrate layer (A) has a thickness of 20 μm to 500 μm.

[0030] In one embodiment, the thickness of each of the adhesive layer (B1) and the adhesive layer (B2) is 10 μm to 200 μm.

[0031] In one embodiment, the double-sided adhesive tape according to the embodiment of the present invention is used for electronic devices.

[0032] Effects of the Invention

[0033] According to the present invention, a double-sided adhesive tape can be provided which has excellent initial adhesion to an adherend, can be sufficiently stretched, is not easily broken even when sufficiently stretched, can be smoothly pulled off from an adherend in a stretched state, and has excellent reworkability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 FIG. 1 is a schematic cross-sectional view of a double-sided adhesive tape according to one embodiment of the present invention.

[0035] Figure 2 (a) Figure 2 (b) Figure 2 (c) is a schematic side view for explaining one mode of pulling and removing the double-sided pressure-sensitive adhesive tape according to one embodiment of the present invention from an adherend.

[0036] Figure 3 (a) Figure 3 (b) Figure 3 (c) is a schematic plan view for explaining one mode of pulling and removing the double-sided pressure-sensitive adhesive tape according to one embodiment of the present invention from an adherend. DETAILED DESCRIPTION

[0037] In this specification, when the term "(meth)acrylic acid" exists, it means "acrylic acid and / or methacrylic acid", and when the term "(meth)acrylate" exists, it means "acrylate and / or methacrylate".

[0038] 《《1. Double-sided adhesive tape》》

[0039] The double-sided adhesive tape in the embodiment of the present invention may be in a roll form or in a sheet form. The double-sided adhesive tape in the embodiment of the present invention may be processed into various shapes.

[0040] The double-sided adhesive tape in the embodiment of the present invention has an adhesive layer (B1), a substrate layer (A) and an adhesive layer (B2) in sequence. As long as the double-sided adhesive tape in the embodiment of the present invention has an adhesive layer (B1), a substrate layer (A) and an adhesive layer (B2) in sequence, any appropriate other layer can be provided within the scope of not damaging the effect of the present invention. The double-sided adhesive tape in the embodiment of the present invention typically has a structure in which an adhesive layer (B1), a substrate layer (A) and an adhesive layer (B2) are stacked in sequence.

[0041] like Figure 1 As shown, double-sided adhesive tape 200 in the embodiment of the present invention typically has adhesive layer (B1) 21 on one surface side of substrate layer (A) 10 and adhesive layer (B2) 22 on the other surface side of substrate layer (A).

[0042] In order to protect the exposed surface, a release liner may be provided on the surface of the adhesive layer (B1) opposite to the substrate layer (A) and the surface of the adhesive layer (B2) opposite to the substrate layer (A). As the release liner, any appropriate release liner may be used. As such a release liner, for example, a release liner having a release treatment layer on the surface of a liner substrate such as a resin film or paper, a release liner containing a low-adhesive material such as a fluorinated polymer (polytetrafluoroethylene, etc.) or a polyolefin resin (polyethylene (PE), polypropylene (PP), etc.), etc. The release treatment layer may be, for example, a release treatment layer formed by treating the surface of the liner substrate with a release treatment agent such as a polysiloxane release treatment agent, a long-chain alkyl release treatment agent, a fluorinated release treatment agent, or a molybdenum sulfide release treatment agent.

[0043] The total thickness of the double-sided adhesive tape in the embodiment of the present invention is preferably 100 μm to 700 μm, more preferably 120 μm to 600 μm, further preferably 150 μm to 500 μm, and particularly preferably 200 μm to 450 μm. If the total thickness of the double-sided adhesive tape in the embodiment of the present invention is within the above range, sufficient adhesiveness and reworkability can be achieved.

[0044] In the double-sided adhesive tape in the embodiment of the present invention, the thickness of the substrate layer (A) is preferably 20 μm to 500 μm, more preferably 50 μm to 450 μm, further preferably 80 μm to 400 μm, and particularly preferably 90 μm to 350 μm. If the thickness of the substrate layer (A) in the double-sided adhesive tape in the embodiment of the present invention is within the above range, it can be fully stretched, and even if it is fully stretched, it is not easy to break, and it can be smoothly pulled and removed from the adherend in the stretched state.

[0045] In the double-sided adhesive tape in the embodiment of the present invention, the thickness of the adhesive layer (B1) and the adhesive layer (B2) are each preferably 10 μm to 200 μm, more preferably 20 μm to 170 μm, further preferably 30 μm to 140 μm, and particularly preferably 40 μm to 110 μm. If the thickness of the adhesive layer (B1) and the adhesive layer (B2) in the double-sided adhesive tape in the embodiment of the present invention are each within the above range, sufficient adhesiveness can be ensured.

[0046] From the viewpoint of pulling and removing, the double-sided adhesive tape in the embodiment of the present invention preferably has a long-sized part. Thus, by grabbing and pulling one end of the length direction of the part formed into the long-sized shape in the double-sided adhesive tape pasted on the adherend, the double-sided adhesive tape can be well removed from the adherend. The shape of the above-mentioned long-sized part is typically band-shaped. From the viewpoint of pulling and removing, the above-mentioned long-sized part can have a shape that tapers toward one end of the length direction. In a more preferred embodiment, the whole of the double-sided adhesive tape is formed into a long-sized shape. From the viewpoint of pulling and removing operability, it is preferred to be provided with a projection (grip) at one end of the length direction of the double-sided adhesive tape. As the shape of the projection, any appropriate shape can be adopted. As such a shape, for example, a shape (such as a rectangle) that can be grasped with a finger can be cited.

[0047] The initial adhesive force of each of the adhesive layer (B1) and the adhesive layer (B2) of the double-sided adhesive tape in the embodiment of the present invention to the SUS plate is preferably 5N / 10mm or more, more preferably 8N / 10mm or more, further preferably 10N / 10mm or more, and particularly preferably 12N / 10mm or more, and the initial adhesive force is the initial adhesive force to the SUS plate under the conditions of 23°C, 50%RH, 180 degrees peeling angle, and 300mm / min peeling speed specified in JIS-Z-0237-2000. If the above initial adhesive force is within the above range, the double-sided adhesive tape in the embodiment of the present invention has excellent initial adhesion to the adherend, for example, it can be effectively used for fixing or temporarily fixing the components possessed by electronic equipment. It should be noted that the upper limit of the above initial adhesive force is preferably 24N / 10mm or less, more preferably 22N / 10mm or less, further preferably 20N / 10mm or less, and particularly preferably 18N / 10mm or less. When the upper limit of the initial adhesive force is too high, the double-sided adhesive tape is too strongly attached to the adherend, so that the effect of the present invention may not be exhibited.

[0048] The initial adhesive force of each of the adhesive layer (B1) and the adhesive layer (B2) of the double-sided adhesive tape in the embodiment of the present invention to a polypropylene (PP) plate is preferably 1 N / 10 mm or more, more preferably 1.5 N / 10 mm or more, further preferably 2 N / 10 mm or more, and particularly preferably 2.5 N / 10 mm or more, the initial adhesive force being the initial adhesive force to a polypropylene (PP) plate under the conditions of 23° C., 50% RH, a peeling angle of 180 degrees, and a peeling speed of 300 mm / min as specified in JIS-Z-0237-2000. If the initial adhesive force is within the above range, the double-sided adhesive tape in the embodiment of the present invention has excellent initial adhesiveness to an adherend, particularly excellent initial adhesiveness to a polyolefin adherend, and can be effectively used, for example, for fixing or temporarily fixing a polyolefin component of an electronic device. It should be noted that the upper limit of the initial adhesive force is preferably below 24N / 10mm, more preferably below 22N / 10mm, further preferably below 20N / 10mm, and particularly preferably below 18N / 10mm. When the upper limit of the initial adhesive force is too high, the double-sided adhesive tape is too strongly attached to the adherend, and therefore may not be able to show the effect of the present invention.

[0049] The initial adhesive force of each of the adhesive layer (B1) and the adhesive layer (B2) of the double-sided adhesive tape in the embodiment of the present invention to the polycarbonate plate is preferably 5 N / 10 mm or more, more preferably 8 N / 10 mm or more, further preferably 10 N / 10 mm or more, and particularly preferably 12 N / 10 mm or more, the initial adhesive force being the initial adhesive force to the polycarbonate plate under the conditions of 23° C., 50% RH, a peeling angle of 180 degrees, and a peeling speed of 300 mm / min as specified in JIS-Z-0237-2000. If the initial adhesive force is within the above range, the double-sided adhesive tape in the embodiment of the present invention has excellent initial adhesiveness to the adherend, particularly excellent initial adhesiveness to the polycarbonate adherend, and can be effectively used, for example, for fixing or temporarily fixing polycarbonate components of electronic devices. It should be noted that the upper limit of the initial adhesive force is preferably below 24N / 10mm, more preferably below 22N / 10mm, further preferably below 20N / 10mm, and particularly preferably below 18N / 10mm. When the upper limit of the initial adhesive force is too high, the double-sided adhesive tape is too strongly attached to the adherend, and therefore may not be able to show the effect of the present invention.

[0050] The initial adhesive force of each of the adhesive layer (B1) and the adhesive layer (B2) of the double-sided adhesive tape in the embodiment of the present invention to the copper (Cu) plate is preferably 7 N / 10 mm or more, more preferably 10 N / 10 mm or more, further preferably 11 N / 10 mm or more, and particularly preferably 13 N / 10 mm or more, the initial adhesive force being the initial adhesive force to the copper (Cu) plate under the conditions of 23° C., 50% RH, a peeling angle of 180 degrees, and a peeling speed of 300 mm / min as specified in JIS-Z-0237-2000. If the initial adhesive force is within the above range, the double-sided adhesive tape in the embodiment of the present invention has excellent initial adhesiveness to the adherend, especially excellent initial adhesiveness to the copper-containing adherend, and can be effectively used, for example, for fixing or temporarily fixing the copper-containing parts of electronic devices. It should be noted that the upper limit of the initial adhesive force is preferably below 24N / 10mm, more preferably below 22N / 10mm, further preferably below 20N / 10mm, and particularly preferably below 18N / 10mm. When the upper limit of the initial adhesive force is too high, the double-sided adhesive tape is too strongly attached to the adherend, and therefore may not be able to show the effect of the present invention.

[0051] The elongation at break of the double-sided adhesive tape in the embodiment of the present invention measured by the determination method of "elongation" specified in JIS-K-7311-1995 is preferably 600% or more, more preferably 650% or more, further preferably 700% or more, particularly preferably 750% or more, and most preferably 800% or more. If the elongation at break is within the above range, the double-sided adhesive tape in the embodiment of the present invention can be fully elongated, and even if fully elongated, it is not easy to break. It should be noted that, from the viewpoint of showing the effect of the present invention in a balanced manner, the upper limit of the elongation at break is preferably 2500% or less.

[0052] The tensile strength of the double-sided adhesive tape in the embodiment of the present invention when stretched by 600%, measured by the measuring method of "elongation" specified in JIS-K-7311-1995, is preferably 12N / 10mm or more, more preferably 15N / 10mm or more, further preferably 20N / 10mm or more, further preferably 25N / 10mm or more, further preferably 30N / 10mm or more, particularly preferably 35N / 10mm or more, and most preferably 40N / 10mm or more. If the tensile strength of the double-sided adhesive tape when stretched by 600% is within the above range, it is not easy to break even if it is fully stretched. It should be noted that, from the viewpoint of showing the effect of the present invention in a balanced manner, the upper limit of the tensile strength of the double-sided adhesive tape when stretched by 600% is preferably 100N / 10mm or less.

[0053] The double-sided adhesive tape in the embodiment of the present invention preferably has excellent performance in being removed by being pulled out from between the adherends (pull-out removability). Here, pull-out removability refers to the ease of removal in the following manner: a portion of the double-sided adhesive tape (typically a protruding portion) is exposed in advance from the two adherends fixed by the double-sided adhesive tape, the exposed portion is pulled, and the double-sided adhesive tape is pulled out, thereby releasing the fixation of the adherends (typically bonding). It should be noted that the two adherends can be two parts of a component. In the following, by Figure 2 , Figure 3 The following will be described in detail.

[0054] Figure 2 1 is a side view schematic diagram for explaining a method of pulling and removing (typically pulling and removing), Figure 2 (a) is a diagram showing the state where the double-sided adhesive tape is started to be pulled away, Figure 2 (b) is a diagram showing a state where the double-sided adhesive tape is being pulled and removed. Figure 2 (c) is a diagram showing a state where the double-sided adhesive tape has been pulled away. Figure 3 Schematic diagram of a top view for explaining one method of pulling and removing (typically pulling and removing), Figure 3(a)~ Figure 3 (c) are respectively Figure 2 (a)~ Figure 2 (c) The corresponding figure.

[0055] like Figure 2 (a) Figure 3 As shown in (a), a protrusion T that is exposed to the outside when the adherend A and the adherend B are joined is provided on the double-sided adhesive tape 200. The adherend A and the adherend B are joined using the double-sided adhesive tape 200. Then, after the joining purpose is achieved, the protrusion T is pinched with fingers, and the double-sided adhesive tape 200 is pulled out from between the adherend A and the adherend B. Then, the double-sided adhesive tape 200 begins to stretch, shrinks in a direction orthogonal to the pulling direction, and begins to peel off from the adherend A and the adherend B (refer to Figure 2 (b) Figure 3 (b)). Then, the entire adhesive area of ​​the double-sided adhesive tape 200 is finally peeled off, thereby completing the removal of the double-sided adhesive tape 200 from between the adherends A and B (refer to Figure 2 (c) Figure 3 (c)). The detachment of the adherend B joined to the adherend A is also completed at the same time.

[0056] Such a double-sided adhesive tape with excellent pulling and removing properties is suitable for fixing or temporarily fixing parts of electronic devices, typically mobile devices such as mobile phones, smart phones, and tablet terminals. For example, when a double-sided adhesive tape is used to fix or temporarily fix parts of an electronic device, sometimes it is necessary to peel off the double-sided adhesive tape and rework due to a defect in the sticking operation of the double-sided adhesive tape, or sometimes it is necessary to peel off the double-sided adhesive tape in order to repair, replace, inspect, or recycle a component having an adherend to which the double-sided adhesive tape is stuck. As such, when a double-sided adhesive tape is used to fix or temporarily fix parts of an electronic device, for example, the frequency of removing the double-sided adhesive tape is particularly high. However, in order to peel off the double-sided adhesive tape from the adherend, such as Figure 2 , Figure 3 As shown, in the case where there are adherends on both sides of the double-sided adhesive tape, for example, it is necessary to first peel off one adherend from the other adherend to expose one side of the double-sided adhesive tape, and then peel off the double-sided adhesive tape. In addition, in the case where there is an adherend on one side of the double-sided adhesive tape, for example, it is necessary to carefully peel off the double-sided adhesive tape from the adherend. However, since the components of electronic devices are often expensive, when performing the peeling operation and the stripping operation as described above, the possibility of damage to the components is high, which is problematic in terms of cost. The double-sided adhesive tape in the embodiment of the present invention is preferably excellent in pulling removal properties, so as Figure 2 , Figure 3As shown, the double-sided adhesive tape can be removed from the adherend in the horizontal direction (shearing direction), so damage to the adherend caused by removing the double-sided adhesive tape can be suppressed.

[0057] It should be noted that, according to the configuration position of the adherend (for example, the configuration position of the components of the adherend in the electronic device), the double-sided adhesive tape cannot be removed from the adherend in the horizontal direction (shear direction) in most cases when removed. In such a case, within the scope of not damaging the effect of the present invention, the double-sided adhesive tape can be pulled and removed at any appropriate angle relative to the adhesive surface. For example, relative to the horizontal direction (shear direction), it is preferably greater than 0 degree and less than or equal to 90 degrees, more preferably greater than 0 degree and less than or equal to 45 degrees, further preferably greater than 0 degree and less than or equal to 30 degrees, and particularly preferably greater than 0 degree and less than or equal to 20 degrees.

[0058] Of course, as long as the purpose can be effectively utilized by showing the effect of the present invention, the double-sided adhesive tape in the embodiment of the present invention can also be used for purposes other than fixing or temporarily fixing the parts possessed by electronic equipment. For example, building components such as wall surfaces or pillars, furniture, home appliances, glass surfaces, etc. can be listed.

[0059] 《1-1. Base material layer (A)》

[0060] In order to fully demonstrate the effects of the present invention, the substrate layer (A) preferably contains at least one selected from the group consisting of polyolefins, thermoplastic polyurethanes and styrene polymers as a resin component. The type of resin contained in the substrate layer (A) may be only one type or two or more types.

[0061] From the perspective of being able to more fully demonstrate the effects of the present invention, the content of the resin component in the substrate layer (A) is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, further preferably 90% by weight to 100% by weight, further preferably 95% by weight to 100% by weight, particularly preferably 98% by weight to 100% by weight, and most preferably substantially 100% by weight.

[0062] In addition, in this specification, when it is described as "substantially 100 weight %", it means that a trace amount of impurities etc. may be contained within the range which does not impair the effect of the present invention, and it may be generally referred to as "100 weight %".

[0063] As the polyolefin, any appropriate polyolefin can be adopted within the scope of not damaging the effect of the present invention. As such a polyolefin, from the aspect of being able to more fully show the effect of the present invention, it is preferably at least one selected from the group consisting of polyethylene, polypropylene and poly-1-butene, and more preferably at least one selected from the group consisting of polyethylene and polypropylene.

[0064] Examples of the polyethylene include at least one selected from the group consisting of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), ultra-low-density polyethylene, medium-density polyethylene (MDPE), high-density polyethylene (HDPE), and ultra-high-density polyethylene.

[0065] The polyethylene may be a metallocene-type polyethylene obtained using a metallocene catalyst. As the polyethylene, a commercially available product may be used.

[0066] As the polypropylene, for example, at least one selected from the group consisting of random polypropylene, block polypropylene and homopolypropylene can be cited.

[0067] The polypropylene may be a metallocene-type polypropylene obtained by using a metallocene catalyst. As the polypropylene, a commercially available product may be used.

[0068] The polybutene-1 may be a metallocene-type polybutene-1 obtained by using a metallocene catalyst. As the polybutene-1, a commercially available product may be used.

[0069] As thermoplastic polyurethane, any appropriate thermoplastic polyurethane can be adopted within the scope of not damaging the effect of the present invention. As such thermoplastic polyurethane, a block copolymer comprising a hard segment and a soft segment called TPU can be generally cited. As such thermoplastic polyurethane, from the aspect of being able to more fully show the effect of the present invention, preferably at least one selected from the group consisting of polyester TPU, polyether TPU and polycarbonate TPU can be cited.

[0070] As the thermoplastic polyurethane, a commercially available product can be used.

[0071] As the styrene polymer, any appropriate styrene polymer may be adopted within the range not impairing the effects of the present invention. As such a styrene polymer, a polymer containing a styrene thermoplastic elastomer is preferably mentioned from the viewpoint that the effects of the present invention can be more fully exhibited.

[0072] Examples of styrene-based thermoplastic elastomers include AB-type block polymers such as hydrogenated styrene-butadiene rubber (HSBR), styrene-based block copolymers or hydrogenated products thereof, styrene-butadiene copolymers (SB), styrene-isoprene copolymers (SI), copolymers of styrene-ethylene-butylene copolymers (SEB), and copolymers of styrene-ethylene-propylene copolymers (SEP); styrene-butadiene rubber (SBR) and other styrene-based random copolymers; ABC-type styrene-olefin crystal block polymers such as styrene-ethylene-butylene copolymer-olefin crystal copolymers (SEBC); and hydrogenated products thereof; etc. As styrene-based thermoplastic elastomers, from the perspective of being able to more fully demonstrate the effects of the present invention, preferably at least one selected from the group consisting of hydrogenated styrene-butadiene rubber (HSBR), styrene-based block copolymers or hydrogenated products thereof can be cited.

[0073] Examples of the hydrogenated styrene-butadiene rubber (HSBR) include DYNARON 1320P, 1321P, and 2324P manufactured by JSR.

[0074] Examples of styrene block copolymers include styrene ABA block copolymers (triblock copolymers) such as styrene-butadiene-styrene copolymer (SBS) and styrene-isoprene-styrene copolymer (SIS); styrene ABAB block copolymers (tetrablock copolymers) such as styrene-butadiene-styrene-butadiene copolymer (SBSB) and styrene-isoprene-styrene-isoprene copolymer (SISI); styrene ABABA block copolymers (pentablock copolymers) such as styrene-butadiene-styrene-butadiene-styrene copolymer (SBSBS) and styrene-isoprene-styrene-isoprene-styrene copolymer (SISIS); styrene block copolymers having more AB repeating units; and the like.

[0075] Examples of hydrogenated products of styrene block copolymers include styrene-ethylene-butylene copolymer-styrene copolymer (SEBS), styrene-ethylene-propylene copolymer-styrene copolymer (SEPS), and styrene-ethylene-butylene copolymer-styrene-ethylene-butylene copolymer (SEBSEB).

[0076] Examples of the styrene-ethylene-butylene copolymer-styrene copolymer (SEBS) include DYNARON 8601P and 9901P manufactured by JSR.

[0077] From the perspective of being able to more fully demonstrate the effects of the present invention, the styrene content in the styrene thermoplastic elastomer (the styrene block content in the case of a styrene block copolymer) is preferably 1% by weight to 40% by weight, more preferably 5% by weight to 40% by weight, further preferably 7% by weight to 30% by weight, further preferably 9% by weight to 20% by weight, particularly preferably 9% by weight to 15% by weight, and most preferably 9% by weight to 13% by weight.

[0078] As the styrene-based thermoplastic elastomer, from the perspective of being able to more fully demonstrate the effects of the present invention, hydrogenated products of styrene-based block copolymers having a repeating structure (ABA type, ABAB type, ABABA type, etc.) of a triblock copolymer or higher containing styrene (A) and butadiene (B) are preferred (SEBS, SEBSEB, SEBSEBS, etc.).

[0079] In the case where the styrene-based thermoplastic elastomer is a hydrogenated product (SEBS, SEBSEB, SEBSEBS, etc.) of a styrene-based block copolymer having a repeating structure (ABA type, ABAB type, ABABA type, etc.) of a triblock copolymer of styrene (A) and butadiene (B), the proportion of the butene structure in the ethylene-butene copolymer block is preferably 60% by weight or more, more preferably 70% by weight or more, and further preferably 75% by weight or more, from the perspective of being able to more fully demonstrate the effects of the present invention. The proportion of the butene structure in the ethylene-butene copolymer block is preferably 90% by weight or less.

[0080] The styrene polymer may contain any other appropriate polymer other than the styrene polymer within the range that does not impair the effect of the present invention. Examples of such other polymers include ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, ethylene-acrylate copolymers, ethylene-methacrylate copolymers, ethylene-1-butene copolymers, ethylene-propylene-1-butene copolymers, ethylene-α-olefin copolymers having 5 to 12 carbon atoms, ethylene-non-conjugated diene copolymers, and the like, preferably ethylene-vinyl acetate copolymers.

[0081] As a preferred embodiment of the styrene-based polymer, for example, a blend of a hydrogenated product of a styrene-based block copolymer (SEBS, SEBSEB, SEBSEBS, etc.) and an ethylene-vinyl acetate copolymer can be cited. From the perspective of being able to more fully demonstrate the effects of the present invention, a blend of SEBS and an ethylene-vinyl acetate copolymer is preferably cited.

[0082] The substrate layer (A) may be one layer (single layer) or two or more layers (multilayers). From the perspective of being able to more fully demonstrate the effects of the present invention, a preferred embodiment when the substrate layer (A) is two or more layers (multilayers) is a two-material three-layer substrate layer with a structure of X layer / Y layer / X layer, and herein, "a two-material three-layer substrate layer with a structure of X layer / Y layer / X layer" refers to a two-material three-layer substrate layer formed by sequentially stacking an X layer, a Y layer, and an X layer.

[0083] When the substrate layer (A) is a two-material three-layer substrate layer having a structure of X layer / Y layer / X layer, any appropriate ratio can be adopted as long as the effect of the present invention is not impaired as to the ratio of the thickness of the three layers. As such a ratio, from the aspect of being able to more fully demonstrate the effect of the present invention, the thickness ratio of X layer / Y layer / X layer is preferably (7.5% to 32.5%) / (35% to 85%) / (7.5% to 32.5%), more preferably (10% to 30%) / (40% to 80%) / (10% to 30%), further preferably (12.5% ​​to 27.5%) / (45% to 75%) / (12.5% ​​to 27.5%), and particularly preferably (15% to 25%) / (50% to 70%) / (15% to 25%).

[0084] When the substrate layer (A) is a two-material three-layer substrate layer having a structure of X layer / Y layer / X layer, specific examples include, from the aspect of being able to more fully demonstrate the effects of the present invention, a two-material three-layer substrate layer having a layer structure of polypropylene / ethylene-vinyl acetate copolymer / polypropylene (a two-material three-layer substrate layer constituted by laminating a polypropylene layer, an ethylene-vinyl acetate copolymer layer, and a polypropylene layer in this order), and a two-material three-layer substrate layer having a layer structure of polyethylene / polypropylene / polyethylene (a two-material three-layer substrate layer constituted by laminating a polyethylene layer, a polypropylene layer, and a polyethylene layer in this order).

[0085] The substrate layer (A) may contain any appropriate additive as required. As additives that may be contained in the substrate layer (A), for example, release agents, ultraviolet light absorbers, heat stabilizers, fillers, lubricants, colorants (dyes, etc.), antioxidants, anti-fouling agents, anti-adhesion agents, foaming agents, polyethyleneimine, etc. may be listed. These additives may be only one or more than two. The additive content in the substrate layer (A) is preferably less than 10% by weight, more preferably less than 7% by weight, further preferably less than 5% by weight, particularly preferably less than 2% by weight, and most preferably less than 1% by weight.

[0086] As the release agent, for example, fatty acid amide release agents, polysiloxane release agents, fluorine-containing release agents, long-chain alkyl release agents, etc. can be cited. From the viewpoint of being able to form a release layer with a better balance between releasability and contamination caused by seepage, fatty acid amide release agents are preferred, and saturated fatty acid bisamides are more preferred. The content of the release agent can be any appropriate content. Typically, it is preferably 0.01% by weight to 5% by weight relative to the resin component in the substrate layer (A).

[0087] Examples of the ultraviolet absorber include benzotriazole compounds, benzophenone compounds, and benzoate compounds. The content of the ultraviolet absorber may be any appropriate content as long as it does not ooze out during molding. Typically, it is preferably 0.01% to 5% by weight relative to the resin component in the substrate layer (A).

[0088] Examples of heat-resistant stabilizers include hindered amine compounds, phosphorus-containing compounds, and cyanoacrylate compounds. The content of the heat-resistant stabilizer may be any appropriate content as long as it does not ooze out during molding. Typically, it is preferably 0.01% to 5% by weight relative to the resin component in the substrate layer (A).

[0089] As fillers, for example, inorganic fillers such as talc, titanium oxide, calcium oxide, magnesium oxide, zinc oxide, titanium oxide, calcium carbonate, silica, clay, mica, barium sulfate, whiskers, and magnesium hydroxide can be cited. The average particle size of the filler is preferably 0.1 μm to 20 μm. The content of the filler can be any appropriate content. Typically, it is preferably 1% by weight to 200% by weight relative to the resin component in the substrate layer (A).

[0090] 《1-2. Adhesive layer (B1), adhesive layer (B2)》

[0091] The adhesive layer (B1) and the adhesive layer (B2) may each be a single layer (single layer) or two or more layers (multilayers). When the adhesive layer (B1) or the adhesive layer (B2) is two or more layers (multilayers), each layer may be a layer containing the same composition or at least one different layer.

[0092] The adhesive layer (B1) and the adhesive layer (B2) may have the same composition or different compositions. In consideration of ease of production and cost, the adhesive layer (B1) and the adhesive layer (B2) are preferably layers having the same composition.

[0093] In the present invention, the description of the adhesive layer (B1) and the adhesive layer (B2) is common, and therefore, in the description of the adhesive layer (B1) and the adhesive layer (B2), it may be simply referred to as "adhesive layer (B)" as a concept including both.

[0094] As the adhesive layer (B), an adhesive layer composed of any appropriate adhesive can be used. Such an adhesive is typically formed by an adhesive composition comprising a base polymer. It should be noted that "base polymer" refers to the main component of the polymer component contained in the adhesive composition (typically a component with a content greater than 50% by weight).

[0095] As the adhesive constituting the adhesive layer (B), any appropriate adhesive may be adopted within the range not impairing the effects of the present invention. As such an adhesive, preferably, at least one selected from the group consisting of acrylic adhesives and rubber adhesives can be cited.

[0096] <1-2-1. Acrylic adhesive>

[0097] One embodiment of the PSA layer (B) is an acrylic PSA containing an acrylic polymer as a main component (base polymer) of the polymer component. That is, the main component (base polymer) of the polymer component contained in the PSA composition forming the acrylic PSA is an acrylic polymer.

[0098] In the adhesive composition forming the acrylic adhesive, the content ratio of the polymer component (including the acrylic polymer as the base polymer) relative to 100 weight % of the adhesive composition is preferably 35 weight % to 85 weight %, more preferably 40 weight % to 80 weight %, further preferably 45 weight % to 75 weight %, and particularly preferably 50 weight % to 70 weight %.

[0099] (1-2-1-1. Polymer component)

[0100] The content ratio of the acrylic polymer as a base polymer in the polymer component contained in the adhesive composition forming the acrylic adhesive is preferably 50% to 100% by weight, more preferably 70% to 100% by weight, further preferably 80% to 100% by weight, and particularly preferably 90% to 100% by weight, relative to 100% by weight of the polymer component.

[0101] As the acrylic polymer, a polymer of a monomer composition containing an alkyl (meth)acrylate as a main monomer and a secondary monomer copolymerizable with the main monomer is preferred. The lower limit of the content of the alkyl (meth)acrylate relative to 100% by weight of the total monomer components is preferably greater than 50% by weight, more preferably 70% by weight or more, further preferably 85% by weight or more, and particularly preferably 90% by weight or more. The upper limit of the content of the alkyl (meth)acrylate relative to 100% by weight of the total monomer components is preferably 99.5% by weight or less, more preferably 99% by weight or less.

[0102] The (meth)acrylic acid alkyl ester may be used alone or in combination of two or more.

[0103] Examples of the alkyl (meth)acrylate include compounds represented by the general formula (1).

[0104] CH2=C(R 1 )COOR 2 (1)

[0105] In the general formula (1), R 1 is a hydrogen atom or a methyl group, R 2 It is an alkyl group having 1 to 20 carbon atoms.

[0106] In order to more fully demonstrate the effect of the present invention, R 1 Preferred is a hydrogen atom.

[0107] In order to more fully demonstrate the effect of the present invention, R 2 An alkyl group having 1 to 14 carbon atoms is preferred, an alkyl group having 2 to 10 carbon atoms is more preferred, an alkyl group having 2 to 8 carbon atoms is further preferred, and an alkyl group having 4 to 8 carbon atoms is particularly preferred. The alkyl group may be linear or branched.

[0108] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.

[0109] From the viewpoint of being able to more fully exhibit the effects of the present invention, the (meth)acrylic acid alkyl ester is preferably at least one selected from the group consisting of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA), and from the viewpoint of adhesive properties, prevention of adhesive residue, etc., n-butyl acrylate (BA) is more preferred.

[0110] When using R in the general formula (1) 1 is a hydrogen atom, R 2 In the case of an alkyl (meth)acrylate having an alkyl group having 4 to 8 carbon atoms (sometimes referred to as a C4-8 alkyl acrylate) as the alkyl (meth)acrylate, the content ratio of the C4-8 alkyl acrylate in all the alkyl (meth)acrylates contained in all the monomer components is preferably 70 to 100% by weight, more preferably 80 to 100% by weight, further preferably 90 to 100% by weight, particularly preferably 95 to 100% by weight, and most preferably substantially 100% by weight, relative to 100% by weight of all the alkyl (meth)acrylates, from the viewpoint of being able to more fully exhibit the effects of the present invention.

[0111] The secondary monomer is copolymerizable with the (meth)acrylic acid alkyl ester which is the primary monomer, and can contribute to the introduction of crosslinking points into the acrylic polymer or the improvement of the cohesive force of the acrylic polymer.

[0112] Examples of the secondary monomer include functional group-containing monomers such as carboxyl-containing monomers, hydroxyl-containing monomers, acid anhydride-containing monomers, amide-containing monomers, amino-containing monomers, ketone-containing monomers, monomers having a nitrogen atom-containing ring, alkoxysilyl-containing monomers, imide-containing monomers, and epoxy-containing monomers. The secondary monomer is preferably at least one selected from the group consisting of carboxyl-containing monomers and hydroxyl-containing monomers in order to more fully demonstrate the effects of the present invention.

[0113] The secondary monomer may be only one kind or two or more kinds.

[0114] As the carboxyl group-containing monomer, from the viewpoint of more fully expressing the effects of the present invention, preferably, at least one selected from the group consisting of acrylic acid (AA) and methacrylic acid (MAA) is used, and acrylic acid (AA) is more preferred.

[0115] Examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; unsaturated alcohols; etc. Among them, hydroxyalkyl (meth)acrylates are preferred, and at least one selected from the group consisting of 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA) is more preferred, from the perspective of being able to more fully demonstrate the effects of the present invention.

[0116] Examples of the acid anhydride group-containing monomer include maleic anhydride, itaconic anhydride, and anhydrides of the above-mentioned carboxyl group-containing monomers.

[0117] Examples of the amide group-containing monomer include acrylamide, methacrylamide, diethylacrylamide, N-methylol(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N'-methylenebisacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, and diacetoneacrylamide.

[0118] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate.

[0119] Examples of the ketone group-containing monomer include diacetone (meth)acrylamide, diacetone (meth)acrylate, methyl vinyl ketone, and vinyl acetoacetate.

[0120] Examples of the monomer having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone and N-acryloylmorpholine.

[0121] As an alkoxysilyl group-containing monomer, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, etc. are mentioned, for example.

[0122] Examples of the imide group-containing monomer include cyclohexylmaleimide, isopropylmaleimide, N-cyclohexylmaleimide, and itaconimide.

[0123] As an epoxy group-containing monomer, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether, etc. are mentioned, for example.

[0124] The content of the secondary monomer may be any appropriate content within the range that does not impair the effect of the present invention. From the perspective of being able to further demonstrate the effect of the present invention, the lower limit of the content of the secondary monomer in all the monomer components used to constitute the acrylic polymer is preferably 0.5% by weight or more, and more preferably 1% by weight or more. In addition, from the perspective of being able to further demonstrate the effect of the present invention, the upper limit of the content of the secondary monomer in all the monomer components used to constitute the acrylic polymer is preferably 30% by weight or less, more preferably 10% by weight or less, further preferably 8% by weight or less, and particularly preferably 5% by weight or less.

[0125] In the case of using a carboxyl group-containing monomer as a secondary monomer (including the case where the secondary monomer is only one and the case where the secondary monomer is two or more), from the perspective of being able to further demonstrate the effect of the present invention, the lower limit of the content ratio of the carboxyl group-containing monomer in all the monomer components used to constitute the acrylic polymer is preferably 0.1% by weight or more, more preferably 0.2% by weight or more, further preferably 0.5% by weight or more, particularly preferably 0.7% by weight or more, and most preferably 1% by weight or more. In addition, in the case of using a carboxyl group-containing monomer as a secondary monomer (including the case where the secondary monomer is only one and the case where the secondary monomer is two or more), from the perspective of being able to further demonstrate the effect of the present invention, the upper limit of the content ratio of the carboxyl group-containing monomer in all the monomer components used to constitute the acrylic polymer is preferably 10% by weight or less, more preferably 8% by weight or less, further preferably 6% by weight or less, and particularly preferably 5% by weight or less.

[0126] In the case where a hydroxyl-containing monomer is used as a secondary monomer (including the case where there is only one secondary monomer and the case where there are two or more secondary monomers), from the perspective of being able to further demonstrate the effects of the present invention, the lower limit of the content of the hydroxyl-containing monomer in all monomer components used to constitute the acrylic polymer is preferably 0.001% by weight or more, more preferably 0.01% by weight or more, further preferably 0.02% by weight or more, particularly preferably 0.05% by weight or more, and most preferably 0.1% by weight or more. In addition, in the case where a hydroxyl-containing monomer is used as a secondary monomer (including the case where there is only one secondary monomer and the case where there are two or more secondary monomers), from the perspective of being able to further demonstrate the effects of the present invention, the upper limit of the content of the hydroxyl-containing monomer in all monomer components used to constitute the acrylic polymer is preferably 10% by weight or less, more preferably 7% by weight or less, further preferably 5% by weight or less, and particularly preferably 3% by weight or less.

[0127] All monomer components for constituting the acrylic polymer may contain any appropriate other monomers other than the main monomer and the secondary monomer within a range not impairing the effects of the present invention. Examples of such other monomers include sulfonic acid group-containing monomers such as styrenesulfonic acid, allylsulfonic acid, and 2-(meth)acrylamido-2-methylpropanesulfonic acid; phosphoric acid group-containing monomers such as 2-hydroxyethylacryloyl phosphate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; vinyl esters such as vinyl acetate (VAc), vinyl propionate, and vinyl laurate; aromatic vinyl compounds such as styrene, substituted styrenes (α-methylstyrene, etc.), and vinyltoluene; aromatic ring-containing (meth)acrylates such as aryl (meth)acrylates (e.g., phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), and arylalkyl (meth)acrylates (e.g., benzyl (meth)acrylate); olefin monomers such as ethylene, propylene, isoprene, butadiene, and isobutylene; chlorine-containing monomers such as vinyl chloride and vinylidene chloride; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; and macromonomers having a free radical polymerizable vinyl group at the end of a monomer obtained by polymerizing a vinyl group; and the like. The other monomers may be present in one kind or in two or more kinds.

[0128] The content ratio of other monomers can be any appropriate content ratio within the scope that does not impair the effect of the present invention. From the perspective of being able to further demonstrate the effect of the present invention, the lower limit of the content ratio of other monomers in all monomer components used to constitute the acrylic polymer is preferably 0% by weight or more, more preferably 0.01% by weight or more, and even more preferably 0.1% by weight or more. In addition, from the perspective of being able to further demonstrate the effect of the present invention, the upper limit of the content ratio of other monomers in all monomer components used to constitute the acrylic polymer is preferably 30% by weight or less, more preferably 10% by weight or less, even more preferably 8% by weight or less, and particularly preferably 5% by weight or less.

[0129] From the viewpoint of further exhibiting the effects of the present invention, the weight average molecular weight of the acrylic polymer is preferably 150,000 to 1,600,000, more preferably 200,000 to 1,400,000, further preferably 250,000 to 1,200,000, and particularly preferably 300,000 to 1,000,000.

[0130] As a method for producing an acrylic polymer, any appropriate method can be adopted within the range that does not impair the effects of the present invention. As such a method, for example, various polymerization methods known as synthetic methods of acrylic polymers such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization can be appropriately adopted. Among these methods, solution polymerization can be preferably used as a representative method.

[0131] As the polymerization method, photopolymerization by irradiation with UV light (typically photopolymerization in the presence of a photopolymerization initiator), radiation polymerization by irradiation with radiation such as β rays and γ rays, and so-called active energy ray irradiation polymerization can be appropriately used.

[0132] As a method for supplying monomers during polymerization, a batch charging method of supplying all monomer raw materials at once, a continuous supply (dropping) method, a batch supply (dropping) method, or the like can be appropriately adopted.

[0133] The polymerization temperature may be any appropriate polymerization temperature depending on the type of monomer, solvent, polymerization initiator, etc. The lower limit of such polymerization temperature is preferably 20° C. or higher, more preferably 40° C. or higher. The upper limit of such polymerization temperature is preferably 170° C. or lower, more preferably 140° C. or lower.

[0134] As the solvent (polymerization solvent) used in solution polymerization, any appropriate solvent can be used within the range that does not impair the effect of the present invention. Examples of such solvents include aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic hydrocarbons or alicyclic hydrocarbons such as hexane and cyclohexane.

[0135] As the polymerization initiator used in the polymerization, any appropriate polymerization initiator can be used according to the type of polymerization method within the range that does not impair the effect of the present invention. As such a polymerization initiator, for example, there can be listed: azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN); persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; aromatic carbonyl compounds; redox initiators obtained by combining peroxides and reducing agents; etc. The polymerization initiator may be only one or more. As the amount of the polymerization initiator used, any appropriate amount can be used within the range that does not impair the effect of the present invention according to the type of polymerization method. As the amount of such a polymerization initiator used, for example, it is preferably 0.005% by weight to 1% by weight, and more preferably 0.01% by weight to 1% by weight relative to all monomer components used to constitute the acrylic polymer.

[0136] The polymer component contained in the pressure-sensitive adhesive composition forming the acrylic pressure-sensitive adhesive may contain any appropriate other polymer in addition to the acrylic polymer as a base polymer within a range that does not impair the effects of the present invention.

[0137] (1-2-1-2. Tackifying resin)

[0138] The pressure-sensitive adhesive composition forming the acrylic pressure-sensitive adhesive may contain a tackifier resin. The tackifier resin may be one type or two or more types.

[0139] As the tackifying resin, any appropriate tackifying resin can be adopted within the scope that does not impair the effect of the present invention. As such tackifying resin, for example, phenolic tackifying resin, terpene tackifying resin, modified terpene tackifying resin, rosin tackifying resin, hydrocarbon tackifying resin, epoxy tackifying resin, polyamide tackifying resin, elastomer tackifying resin, ketone tackifying resin, etc. can be cited.

[0140] As phenolic tackifying resins, for example, terpene phenol resins, hydrogenated terpene phenol resins, alkylphenol resins, rosin phenol resins, etc. can be cited. Terpene phenol resins refer to polymers containing terpene residues and phenol residues, and are concepts including copolymers of terpenes and phenolic compounds (terpene-phenol copolymer resins) and substances obtained by phenol-modifying homopolymers or copolymers of terpenes (phenol-modified terpene resins). As terpenes constituting such terpene phenol resins, for example, monoterpenes such as α-pinene, β-pinene, and limonene (including d form, l form, and d / l form (limonene (ジペンテン)) can be cited. Hydrogenated terpene phenol resins refer to hydrogenated terpene phenol resins having a structure obtained by hydrogenating such terpene phenol resins, and are sometimes also referred to as hydrogenated terpene phenol resins. Alkylphenol resins are resins obtained from alkylphenols and formaldehyde (oily phenolic resins). Examples of the alkylphenol resin include novolac and resol types. Examples of the rosin phenol resin include phenol-modified products of rosins or various rosin derivatives (including rosin esters, unsaturated fatty acid-modified rosins, and unsaturated fatty acid-modified rosin esters). Examples of the rosin phenol resin include rosin phenol resins obtained by adding phenol to rosins or various rosin derivatives using an acid catalyst and performing thermal polymerization.

[0141] Examples of terpene tackifier resins include polymers of terpenes (typically monoterpenes) such as α-pinene, β-pinene, d-limonene, l-limonene, and limonene. Examples of terpene homopolymers include α-pinene polymers, β-pinene polymers, and limonene polymers.

[0142] Examples of the modified terpene resin include styrene-modified terpene resins and hydrogenated terpene resins.

[0143] The concept of rosin-based tackifying resins includes both rosins and rosin derivative resins. Examples of rosins include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins (hydrogenated rosin, disproportionated rosin, polymerized rosin, and other chemically modified rosins) obtained by modifying these unmodified rosins by hydrogenation, disproportionation, and polymerization.

[0144] Examples of the rosin derivative resin include rosin esters such as unmodified rosin esters which are esters of unmodified rosin and alcohols, and modified rosin esters which are esters of modified rosin and alcohols; unsaturated fatty acid-modified rosins obtained by modifying rosins with unsaturated fatty acids; unsaturated fatty acid-modified rosin esters obtained by modifying rosin esters with unsaturated fatty acids; rosin alcohols obtained by reducing the carboxyl groups of rosins and rosin derivative resins (rosin esters, unsaturated fatty acid-modified rosins, unsaturated fatty acid-modified rosin esters, etc.); metal salts thereof; etc. Examples of the rosin ester include methyl esters, triethylene glycol esters, glycerol esters, pentaerythritol esters, etc. of unmodified rosins or modified rosins (e.g., hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.).

[0145] Examples of the hydrocarbon tackifier resin include aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic / aromatic petroleum resins (styrene-olefin copolymers, etc.), aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone indene resins.

[0146] The content of the tackifier resin in the adhesive composition forming the acrylic adhesive is preferably 1 to 80 parts by weight, more preferably 5 to 70 parts by weight, further preferably 10 to 55 parts by weight, and particularly preferably 15 to 50 parts by weight, relative to 100 parts by weight of the polymer component.

[0147] (1-2-1-3. Cross-linking agent)

[0148] The pressure-sensitive adhesive composition forming the acrylic pressure-sensitive adhesive may contain a cross-linking agent. The cross-linking agent may be one type or two or more types.

[0149] As the crosslinking agent, any appropriate crosslinking agent may be adopted within the range not impairing the effects of the present invention. Examples of such a crosslinking agent include isocyanate crosslinking agents and non-isocyanate crosslinking agents.

[0150] As the isocyanate crosslinking agent, any appropriate isocyanate crosslinking agent can be used within the range that does not impair the effect of the present invention. Examples of such isocyanate crosslinking agents include aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and dimers and trimers of these diisocyanates. Specifically, toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, butane-1,4-diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, dicyclohexylmethane-4,4′-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate, tetramethyl-m-xylylene diisocyanate, and the like, as well as dimers and trimers thereof and polyphenylmethane polyisocyanate can be used. Moreover, as said trimer, an isocyanurate type, a biuret type, an allophanate type, etc. are mentioned.

[0151] As the isocyanate crosslinking agent, a commercial product can be used. Examples of commercially available polyisocyanates include: "Takenate 600" manufactured by Mitsui Chemicals, Inc.; "Duranate TPA100" manufactured by Asahi Kasei Chemicals, Inc.; "Coronate L", "Coronate HL", "Coronate HK", "Coronate HX", "Coronate 2096" manufactured by Nippon Polyurethane Industries, Ltd., etc.

[0152] Examples of the non-isocyanate crosslinking agent include epoxy crosslinking agents, Oxazoline crosslinking agents, aziridine crosslinking agents, melamine crosslinking agents, carbodiimide crosslinking agents, hydrazine crosslinking agents, amine crosslinking agents, peroxide crosslinking agents, metal chelate crosslinking agents, metal alkoxide crosslinking agents, metal salt crosslinking agents, silane coupling agents, etc.

[0153] In a preferred embodiment, an epoxy crosslinking agent can be used as the non-isocyanate crosslinking agent. The epoxy crosslinking agent preferably includes compounds having two or more epoxy groups in one molecule, and more preferably includes epoxy crosslinking agents having three to five epoxy groups in one molecule.

[0154] Specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, etc. Commercially available epoxy crosslinking agents include, for example, products named "TETRAD-C" and "TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd., "EPICRON CR-5L" manufactured by DIC Corporation, "Denacol EX-512" manufactured by Nagase ChemteX Corporation, and "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd.

[0155] The content of the crosslinking agent in the adhesive composition forming the acrylic adhesive is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 8 parts by weight, further preferably 0.5 to 7 parts by weight, and particularly preferably 1.5 to 3.5 parts by weight, relative to 100 parts by weight of the polymer component.

[0156] In the adhesive composition forming the acrylic adhesive, an isocyanate crosslinking agent and a non-isocyanate crosslinking agent (e.g., an epoxy crosslinking agent) may be used together. The content ratio of the non-isocyanate crosslinking agent in the adhesive composition forming the acrylic adhesive is preferably 1 / 50 or less, more preferably 1 / 75 or less, further preferably 1 / 100 or less, and particularly preferably 1 / 150 or less relative to the content ratio of the isocyanate crosslinking agent in the adhesive composition forming the acrylic adhesive. In addition, the content ratio of the non-isocyanate crosslinking agent in the adhesive composition forming the acrylic adhesive is preferably 1 / 1000 or more, more preferably 1 / 500 or more relative to the content ratio of the isocyanate crosslinking agent in the adhesive composition forming the acrylic adhesive.

[0157] (1-2-1-4.Packing)

[0158] The acrylic adhesive preferably contains a filler. That is, the adhesive composition forming the acrylic adhesive preferably contains a filler. The filler may be only one type or two or more types.

[0159] By including fillers in acrylic adhesives, it is possible to help reduce the pull-peel stress during the tensile deformation of the double-sided adhesive tape. Thus, it is possible to achieve a good adhesion during the use of the double-sided adhesive tape and an excellent pull-removability during removal. In detail, the filler contained in the acrylic adhesive can exist in a state exposed on the surface of the adhesive layer (B) or contained in the adhesive layer (B). The filler exposed on the surface of the adhesive layer (B) can reduce the acrylic adhesive area on the surface of the adhesive layer (B) and improve the slippage of the adhesive interface in the shear direction. Thus, the pull-peel stress can be reduced. However, the reduction in the acrylic adhesive area on the surface of the adhesive layer (B) may also lead to a reduction in the initial adhesion of the adhesive layer (B). On the other hand, it can be considered that the filler present in the adhesive layer (B) has a great contribution to the reduction of the pull-peel stress without reducing the initial adhesion. As its main reason, for example, it can be considered that the state change of the adhesive layer (B) accompanied by the deformation of the double-sided adhesive tape. Specifically, the pulling and peeling is a method of peeling the adhesive layer (B) in a direction parallel to the adhesive surface (pulling and peeling direction, shearing direction), so the double-sided adhesive tape is deformed in a direction parallel to the adhesive surface during pulling and peeling. The extensible double-sided adhesive tape is stretched relative to the above pulling, and the adhesive layer (B) is also deformed accordingly. For example, in the case where the substrate layer (A) supporting the adhesive layer (B) has elongation relative to pulling, the adhesive layer (B) is also greatly deformed as the substrate layer (A) is stretched. It can be considered that through the deformation of the adhesive layer (B), the exposure amount of the filler contained in the adhesive layer (B) on the surface of the adhesive layer (B) increases, and the slippage of the adhesive interface in the shearing direction is improved. In addition, it is also considered that the acrylic adhesive in the adhesive layer (B) is deformed due to pulling and peeling, and in contrast, the filler in the adhesive layer (B) shows a different behavior from the acrylic adhesive. It can also be considered that the difference in the behavior of the acrylic adhesive and the filler to the pulling and peeling contributes to the reduction of the pulling and peeling stress. Moreover, the change of the surface state of the adhesive layer and the behavior of the constituent components of the adhesive layer will not become obvious due to the difference in the peeling method, such as 90 degree peeling or 180 degree peeling, or it will be negligible. However, it can be considered that it has a significant impact on the stress change during the pull peeling. As a result, it can be considered that the filler contained in the adhesive layer (B) has a significant contribution to both maintaining the initial adhesion and reducing the pull peeling stress.

[0160] The shape of the filler may be any appropriate shape within the range that does not impair the effects of the present invention. Representative shapes of the filler include particle shapes and fiber shapes, and particle shapes are preferred.

[0161] As fillers, any appropriate fillers can be used within the scope that does not impair the effects of the present invention. As such fillers, from the perspective of being able to further demonstrate the effects of the present invention, for example, metals such as copper, silver, gold, platinum, nickel, aluminum, chromium, iron, and stainless steel; metal oxides such as aluminum oxide, silicon oxide (silicon dioxide), titanium oxide, zirconium oxide, zinc oxide, tin oxide, copper oxide, and nickel oxide; metal hydroxides and hydrated metal compounds such as aluminum hydroxide, boehmite, magnesium hydroxide, calcium hydroxide, zinc hydroxide, silicic acid, iron hydroxide, copper hydroxide, barium hydroxide, zirconium oxide hydrate, tin oxide hydrate, basic magnesium carbonate, hydrotalcite, dawsonite, borax, and zinc borate; carbons such as silicon carbide, boron carbide, nitrogen carbide, and calcium carbide nitrides such as aluminum nitride, silicon nitride, boron nitride, and gallium nitride; carbonates such as calcium carbonate; titanates such as barium titanate and potassium titanate; carbon black, carbon tubes (carbon nanotubes), carbon fibers, diamonds and other carbonaceous materials; inorganic materials such as glass; polymers such as polystyrene, acrylic resins (such as polymethyl methacrylate), phenolic resins, benzoguanamine resins, urea-formaldehyde resins, polysiloxane resins, polyesters, polyurethanes, polyethylene (PE), polypropylene (PP), polyamides (such as nylon, etc.), polyimides, and polyvinylidene chloride; natural raw material particles such as volcanic sand, clay, and sand; synthetic fiber materials; natural fiber materials; etc.

[0162] The average particle size of the filler is preferably less than 50% of the thickness of the adhesive layer (B). Here, in this specification, the average particle size of the filler refers to the particle size (50% median particle size) when the cumulative particle size of the weight basis in the particle size distribution obtained by the measurement based on the sieving method reaches 50%. If the average particle size of the filler is less than 50% of the thickness of the adhesive layer (B), it can be said that more than 50% by weight of the filler particles contained in the adhesive layer (B) have a particle size less than the thickness of the adhesive layer (B). By having more than 50% by weight of the filler particles contained in the adhesive layer (B) have a particle size less than the thickness of the adhesive layer (B), the tendency to maintain a good surface state (such as smoothness) on the surface of the adhesive layer (B) becomes larger. From the viewpoint of improving adhesion by improving adhesion to the adherend, the above situation is preferred.

[0163] From the perspective of being able to further demonstrate the effects of the present invention, the average particle size of the filler is preferably 45% or less, more preferably 40% or less, relative to the thickness of the adhesive layer (B). From the perspective of being able to further demonstrate the effects of the present invention, the average particle size of the filler is preferably greater than 3%, more preferably 4% or more, further preferably 10% or more, further preferably 15% or more, particularly preferably 20% or more, and most preferably 30% or more, relative to the thickness of the adhesive layer (B).

[0164] From the perspective of further demonstrating the effects of the present invention, preferably 60% by weight or more, more preferably 70% by weight or more, and further preferably 80% by weight or more of the fillers contained in the adhesive layer (B) have a particle size smaller than the thickness T of the adhesive layer (B), and preferably substantially all (e.g., 99% by weight or more and 100% by weight or less) of the fillers contained in the adhesive layer (B) have a particle size smaller than the thickness T of the adhesive layer (B).

[0165] From the perspective of further demonstrating the effects of the present invention, preferably 40% by weight or more, more preferably 50% by weight or more, and further preferably 55% by weight or more of the fillers contained in the adhesive layer (B) have a particle size smaller than 2 / 3 of the thickness T of the adhesive layer (B), and preferably 40% by weight or more, more preferably 50% by weight or more, and further preferably 55% by weight or more of the fillers contained in the adhesive layer (B) have a particle size smaller than 1 / 2 of the thickness T of the adhesive layer (B).

[0166] It should be noted that the fact that more than X weight % of the filler has a particle size smaller than Y means that the cumulative particle size (weight basis) up to the particle size Y (μm) in the particle size distribution obtained by the measurement based on the sieving method is smaller than X (weight %). The proportion (weight %) of the filler having a predetermined particle size can be obtained based on the above particle size distribution.

[0167] Among the fillers contained in the adhesive layer (B), particles with a particle size less than 30 μm preferably account for more than 50% by weight, more preferably account for more than 70% by weight, and further preferably account for more than 90% by weight. Even if the thickness of the adhesive layer (B) containing such a filler is relatively small, the smoothness of the surface of the adhesive layer is not easily damaged. Therefore, even if a thinner adhesive layer (B) is made, it is possible to well balance excellent adhesion and excellent pulling removal when removing. This is advantageous from the perspective of reducing the total thickness of the double-sided adhesive tape.

[0168] Among the fillers contained in the adhesive layer (B), particles having a particle size of preferably less than 20 μm, more preferably less than 15 μm, and further preferably less than 10 μm preferably account for 50 wt % or more, more preferably 70 wt % or more, and further preferably 80 wt % or more.

[0169] Among the fillers contained in the adhesive layer (B), the proportion of fillers having a particle size of less than 1 μm is preferably 50% by weight or less. From the viewpoint of reducing the pulling peel stress, the particle size of the filler preferably has a certain degree of size. In addition, for example, from the perspective of productivity such as not causing excessive viscosity increase in the preparation of the adhesive composition, it is preferred to limit the amount of fine particles.

[0170] Among the fillers contained in the adhesive layer (B), the proportion of fillers having a particle size of preferably less than 1 μm, more preferably less than 2 μm, and further preferably less than 5 μm is preferably 30 wt % or less, more preferably 10 wt % or less, and further preferably 5 wt % or less.

[0171] From the perspective of further demonstrating the effects of the present invention, the lower limit of the average particle size of the filler as a whole contained in the adhesive layer (B) is preferably 0.5 μm or more, more preferably 0.8 μm or more, further preferably 1 μm or more, further preferably greater than 1 μm, further preferably 2 μm or more, particularly preferably 3 μm or more, and most preferably 5 μm or more.

[0172] From the perspective of being able to further demonstrate the effects of the present invention, the upper limit value of the average particle size of the filler contained in the adhesive layer (B) is preferably 50 μm or less, more preferably 30 μm or less, further preferably 20 μm or less, further preferably 18 μm or less, further preferably 15 μm or less, particularly preferably 12 μm or less, and most preferably 10 μm or less.

[0173] From the aspect that can further show the effect of the present invention, the average aspect ratio of the filler is preferably less than 100, more preferably less than 50, further preferably less than 10, particularly preferably less than 5, and most preferably less than 2. Here, the average aspect ratio of the filler is calculated by the average value of the aspect ratio of each particle represented by the major diameter / minor diameter of the filler. The major diameter typically refers to the maximum diameter length of the particle to be measured, and the minor diameter typically refers to the minimum diameter length of the particle to be measured. The average aspect ratio can be grasped by transmission electron microscopy.

[0174] In the adhesive layer (B) containing a filler, from the aspect of being able to further express the effect of the present invention, the content ratio of the filler relative to 100 parts by weight of the base polymer contained in the adhesive layer (B) is preferably 0.5 parts by weight to 100 parts by weight, more preferably 1 part by weight to 80 parts by weight, further preferably 3 parts by weight to 70 parts by weight, further preferably 5 parts by weight to 60 parts by weight, further preferably 10 parts by weight to 55 parts by weight, further preferably 15 parts by weight to 50 parts by weight, further preferably 20 parts by weight to 45 parts by weight, particularly preferably 25 parts by weight to 40 parts by weight, and most preferably 30 parts by weight to 40 parts by weight.

[0175] (1-2-1-5. Other additives)

[0176] The adhesive composition forming the acrylic adhesive may contain any other appropriate additives within the range that does not impair the effects of the present invention. Examples of such other additives include: leveling agents, crosslinking aids, plasticizers, softeners, colorants (dyes, pigments), antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, light stabilizers, dispersants, oligomers, etc.

[0177] (1-2-1-6. Formation of Acrylic Adhesive)

[0178] Acrylic adhesives can be formed from adhesive compositions by any appropriate method within the scope of not impairing the effects of the present invention. As such methods, for example, there can be cited: a method (direct method) in which the adhesive composition is applied to any appropriate substrate (e.g., substrate layer (A)) and dried as needed to form an adhesive layer on the substrate; an adhesive composition is applied to a releasable surface (releasable surface) and dried as needed to form an adhesive layer on a releasable surface (releasable surface), and the adhesive layer is transferred to any appropriate substrate (e.g., substrate layer (A)) (transfer method), etc. As a releasable surface (releasable surface), for example, the surface of the aforementioned release liner can be cited.

[0179] As a method for applying the adhesive composition, any appropriate coating method can be adopted within the scope that does not impair the effect of the present invention. As such a coating method, for example, roll coating, gravure coating, reverse coating, roller brushing, spraying, air knife coating, extrusion coating using a die coater, etc., etc. can be cited. In order to cure the coating layer formed by coating, active energy ray irradiation such as ultraviolet irradiation can be performed.

[0180] From the viewpoint of promoting the crosslinking reaction and improving the manufacturing efficiency, the drying of the adhesive composition can be carried out under heating. The drying temperature can be set to 40°C to 150°C, preferably 60°C to 130°C, for example. After the adhesive composition is dried, it can be further aged in order to adjust the component transfer in the adhesive layer (B), perform the crosslinking reaction, relax the strain that may exist in the adhesive layer (B), etc.

[0181] <1-2-2. Rubber adhesive>

[0182] One embodiment of the adhesive layer (B) is a rubber adhesive containing a rubber polymer as a main component (base polymer) of the polymer component. That is, the main component (base polymer) of the polymer component contained in the adhesive composition forming the rubber adhesive is a rubber polymer.

[0183] In the adhesive composition for forming a rubber-based adhesive, the content of the polymer component (including the rubber-based polymer as a base polymer) relative to 100% by weight of the adhesive composition is preferably 20% to 95% by weight, more preferably 30% to 85% by weight, further preferably 40% to 75% by weight, and particularly preferably 50% to 65% by weight.

[0184] (1-2-2-1. Polymer component)

[0185] Among the polymer components contained in the adhesive composition that forms the rubber adhesive, the content ratio of the rubber polymer as the base polymer is preferably 50% to 100% by weight, more preferably 70% to 100% by weight, further preferably 80% to 100% by weight, and particularly preferably 90% to 100% by weight, relative to 100% by weight of the polymer components.

[0186] The rubber-based polymer may typically be at least one selected from the group consisting of natural rubber and synthetic rubber.

[0187] Specific examples of synthetic rubbers include polyisoprene, polybutadiene, polyisobutylene, butyl rubber, ethylene-propylene rubber, propylene-butylene rubber, ethylene-propylene-butylene rubber, styrene-butadiene rubber (SBR), styrene block copolymers, hydrogenated products of styrene block copolymers, graft-modified natural rubbers obtained by grafting other monomers onto natural rubber, and the like.

[0188] Examples of styrene block copolymers include styrene ABA block copolymers (triblock copolymers) such as styrene-butadiene-styrene copolymer (SBS) and styrene-isoprene-styrene copolymer (SIS); styrene ABAB block copolymers (tetrablock copolymers) such as styrene-butadiene-styrene-butadiene copolymer (SBSB) and styrene-isoprene-styrene-isoprene copolymer (SISI); styrene ABABA block copolymers (pentablock copolymers) such as styrene-butadiene-styrene-butadiene-styrene copolymer (SBSBS) and styrene-isoprene-styrene-isoprene-styrene copolymer (SISIS); styrene block copolymers having more AB repeating units; and the like.

[0189] Examples of hydrogenated products of styrene block copolymers include styrene-ethylene-butylene copolymer-styrene copolymer (SEBS), styrene-ethylene-propylene copolymer-styrene copolymer (SEPS), and styrene-ethylene-butylene copolymer-styrene-ethylene-butylene copolymer (SEBSEB).

[0190] The rubber adhesive as one embodiment of the adhesive layer (B) preferably comprises a styrene block copolymer as a base polymer. Typically, the base polymer comprises at least one selected from the group consisting of styrene-butadiene-styrene copolymer (SBS), styrene-isoprene-styrene copolymer (SIS) and styrene-ethylene-butylene copolymer-styrene copolymer (SEBS).

[0191] When the base polymer includes at least one selected from the group consisting of styrene-butadiene-styrene copolymer (SBS), styrene-isoprene-styrene copolymer (SIS) and styrene-ethylene-butylene copolymer-styrene copolymer (SEBS), the total content of styrene-butadiene-styrene copolymer (SBS), styrene-isoprene-styrene copolymer (SIS) and styrene-ethylene-butylene copolymer-styrene copolymer (SEBS) in the base polymer is preferably 70% to 100% by weight, more preferably 80% to 100% by weight, further preferably 90% to 100% by weight, particularly preferably 95% to 100% by weight, and most preferably substantially 100% by weight.

[0192] The styrene content of the styrene block copolymer can be, for example, 5% by weight or more and 40% by weight or less. From the viewpoint of pull-off properties, a styrene block copolymer having a styrene content of 10% by weight or more (more preferably greater than 10% by weight, for example, 12% by weight or more) is generally preferred. In addition, from the viewpoint of adhesion to an adherend and impact resistance, a styrene block copolymer having a styrene content of 35% by weight or less (typically less than 30% by weight, more preferably less than 25% by weight, for example, less than 20% by weight) is preferred. For example, a styrene block copolymer having a styrene content of 12% by weight or more and less than 20% by weight can be preferably used.

[0193] The polymer component contained in the adhesive composition forming the rubber adhesive may contain any appropriate other polymer in addition to the rubber polymer as a base polymer within a range not impairing the effects of the present invention.

[0194] (1-2-2-2. Tackifying resin)

[0195] The adhesive composition forming the rubber-based adhesive may contain a tackifier resin. The tackifier resin may be one type or two or more types.

[0196] As the tackifier resin that may be contained in the pressure-sensitive adhesive composition forming the rubber-based pressure-sensitive adhesive, the tackifier resins described in the section (1-2-1-2. Tackifier resin) may be cited.

[0197] The content of the tackifier resin in the adhesive composition forming the rubber adhesive is preferably 20 to 120 parts by weight, more preferably 30 to 110 parts by weight, further preferably 40 to 100 parts by weight, and particularly preferably 50 to 90 parts by weight, relative to 100 parts by weight of the polymer component.

[0198] (1-2-2-3. Cross-linking agent)

[0199] The adhesive composition forming the rubber adhesive may contain a crosslinking agent. The crosslinking agent may be one type or two or more types.

[0200] As the cross-linking agent that may be contained in the adhesive composition forming the rubber-based adhesive, the cross-linking agents described in the section (1-2-1-3. Cross-linking agent) may be cited.

[0201] The content of the crosslinking agent in the adhesive composition forming the rubber adhesive is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 3 parts by weight, further preferably 0.1 to 2 parts by weight, and particularly preferably 0.2 to 1 part by weight, relative to 100 parts by weight of the polymer component.

[0202] In the adhesive composition forming the rubber adhesive, an isocyanate crosslinking agent and a non-isocyanate crosslinking agent (e.g., an epoxy crosslinking agent) may be used together. The content ratio of the non-isocyanate crosslinking agent in the adhesive composition forming the rubber adhesive is preferably 1 / 50 or less, more preferably 1 / 75 or less, further preferably 1 / 100 or less, and particularly preferably 1 / 150 or less relative to the content ratio of the isocyanate crosslinking agent in the adhesive composition forming the rubber adhesive. In addition, the content ratio of the non-isocyanate crosslinking agent in the adhesive composition forming the rubber adhesive is preferably 1 / 1000 or more, more preferably 1 / 500 or more relative to the content ratio of the isocyanate crosslinking agent in the adhesive composition forming the rubber adhesive.

[0203] (1-2-2-4. Other additives)

[0204] The adhesive composition forming the rubber adhesive may contain any appropriate other additives within the range that does not impair the effect of the present invention. Such other additives include, for example, leveling agents, crosslinking aids, plasticizers, softeners, colorants (dyes, pigments), antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, light stabilizers, dispersants, oligomers, etc.

[0205] (1-2-2-5. Formation of Rubber Adhesive)

[0206] The rubber adhesive can be formed from the adhesive composition by any appropriate method within the scope of not impairing the effect of the present invention. As such a method, for example, the adhesive composition is applied to any appropriate substrate (for example, substrate layer (A)) and dried as needed to form an adhesive layer on the substrate (direct method); the adhesive composition is applied to a releasable surface (release surface) and dried as needed to form an adhesive layer on a releasable surface (release surface), and the adhesive layer is transferred to any appropriate substrate (for example, substrate layer (A)) (transfer method), etc. As a releasable surface (release surface), for example, the surface of the aforementioned release liner can be cited.

[0207] As a method for applying the adhesive composition, any appropriate coating method can be adopted within the scope that does not impair the effect of the present invention. As such a coating method, for example, roll coating, gravure coating, reverse coating, roller brushing, spraying, air knife coating, extrusion coating using a die coater, etc., etc. can be cited. In order to cure the coating layer formed by coating, active energy ray irradiation such as ultraviolet irradiation can be performed.

[0208] From the viewpoint of promoting the crosslinking reaction and improving the manufacturing efficiency, the drying of the adhesive composition can be carried out under heating. The drying temperature can be set to 40°C to 150°C, preferably 60°C to 130°C, for example. After the adhesive composition is dried, it can be further aged in order to adjust the component transfer in the adhesive layer (B), perform the crosslinking reaction, relax the strain that may exist in the adhesive layer (B), etc.

[0209] Example

[0210] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited by these examples in any way. It should be noted that the test and evaluation methods in the examples, etc. are as follows. It should be noted that when "parts" are recorded, unless otherwise specified, they represent "parts by weight", and when "%" is recorded, unless otherwise specified, they represent "% by weight".

[0211] <Initial Adhesion>

[0212] The determination of initial adhesive force is carried out by the following method. A double-sided adhesive tape cut into a size of 10 mm in width and 100 mm in length is prepared. Under an environment of 23°C and 50% RH, the adhesive layer of the prepared double-sided adhesive tape is exposed, and a polyethylene terephthalate (PET) film with a thickness of 25 μm is attached to one surface. Then, another adhesive layer is crimped onto the respective surfaces of SUS304BA plate, polypropylene plate, polycarbonate plate, and copper plate by making a 2kg roller go back and forth once. It is placed under an environment of 23°C and 50% RH for 30 minutes, and then the peel strength (N / 10mm) is measured using a tensile tester according to JIS-Z-0237-2000 under the conditions of a pulling speed of 300 mm / min and a peeling angle of 180 degrees. A universal tensile compression tester (product name "TG-1kN", manufactured by Minebea Co., Ltd.) is used as a tensile tester.

[0213] <Tension test>

[0214] The measurement was carried out according to the measurement method of "elongation" described in JIS-K-7311-1995. More specifically, the elongation at break was measured using a No. 1 dumbbell-shaped test piece (width 10 mm, line spacing 10 mm) at a pulling speed of 300 mm / min. The product name "Autograph AG-10G type tensile tester" manufactured by Shimadzu Corporation was used as a tensile tester. During the test, the powder (Johnson's baby powder (main ingredient: talc)) was applied to the adhesive layer to remove the influence of the viscosity of the adhesive. It should be noted that the pulling direction in the tensile test was made consistent with the length direction of the double-sided adhesive tape. In addition, the tensile strength (N / 10mm) at an elongation of 600% was also measured through this test.

[0215] <Rework test>

[0216] The reworkability test was conducted by the following method. A double-sided adhesive tape cut into a size of 15 mm in width and 50 mm in length was prepared. Under an environment of 23°C and 50% RH, the adhesive layer of the double-sided adhesive tape was exposed, and one adhesive layer was pressed onto the surface of the polycarbonate plate by moving a 2 kg roller back and forth once. Another adhesive layer was pressed onto the copper foil side of the polycarbonate plate laminated with 35 μm copper foil by moving a 2 kg roller back and forth once. At this time, the two sides of the 40 mm long portion of the double-sided adhesive tape were laminated on the polycarbonate plate and the copper foil, so that nothing was laminated on the 10 mm long portion of the double-sided adhesive tape, and the portion was used as a protrusion for extraction. It was placed under an environment of 23°C and 50% RH for 30 minutes, and then the protrusion was pulled out by hand at an angle of 15 degrees perpendicular to the direction of lamination until the adhesive layer of the double-sided adhesive tape was peeled off by 1 cm along the length direction. Then, the double-sided adhesive tape was peeled off at an angle of 0 degrees perpendicular to the direction of lamination. At this time, the following three points were evaluated as reworkability.

[0217] (i) Peelability

[0218] Confirm whether it can be peeled off to the end.

[0219] ○: The peeling can be completed.

[0220] ×: The peeling force was so large that the peeling could not be completed, or the peeling was broken in the middle of the peeling.

[0221] (ii) Damage to copper foil

[0222] Check whether the copper foil is bent.

[0223] ○: The copper foil is not bent.

[0224] ×: The copper foil was bent and damaged.

[0225] (iii) Stripping in multiple steps

[0226] Check whether the peeling can be stopped and pulled several times to see if it can be peeled off.

[0227] ○: Can be peeled off.

[0228] ×: Cannot be peeled off.

[0229] [Manufacturing Example 1]: Manufacture of substrate (1)

[0230] Using polypropylene (propylene-1-butene-α-olefin copolymer type, PP, manufactured by Mitsui Chemicals, Inc.) as the X layer and ethylene-vinyl acetate copolymer (EVA, manufactured by Tosoh Corporation) as the Y layer, two materials three-layer (X layer / Y layer / X layer) extrusion T-die molding machine was used for molding. The extrusion temperature was implemented under the following conditions.

[0231] X layer: 200℃

[0232] Y layer: 200℃

[0233] X layer: 200℃

[0234] Die temperature: 200℃

[0235] The three-layer substrate of two materials PP / EVA / PP (thickness: PP / EVA / PP = 25 μm / 100 μm / 25 μm) is integrated by co-extrusion molding from a T-die, and after it is fully solidified, it is wound into a roll, thereby obtaining a substrate (1) as a wound body (total thickness = 150 μm).

[0236] [Manufacturing Example 2]: Manufacture of substrate (2)

[0237] Using polypropylene (propylene-1-butene-α-olefin copolymer type, PP, manufactured by Mitsui Chemicals, Inc.) as the X layer and ethylene-vinyl acetate copolymer (EVA, manufactured by Tosoh Corporation) as the Y layer, two materials three-layer (X layer / Y layer / X layer) extrusion T-die molding machine was used for molding. The extrusion temperature was implemented under the following conditions.

[0238] X layer: 200℃

[0239] Y layer: 200℃

[0240] X layer: 200℃

[0241] Die temperature: 200℃

[0242] The three-layer substrate of two materials PP / EVA / PP (thickness: PP / EVA / PP = 40 μm / 120 μm / 40 μm) is integrated by co-extrusion molding from a T-die, and after it is fully solidified, it is wound into a roll, thereby obtaining a substrate (2) as a wound body (total thickness = 200 μm).

[0243] [Manufacturing Example 3]: Manufacture of substrate (3)

[0244] Using polypropylene (propylene-1-butene-α-olefin copolymer type, PP, manufactured by Mitsui Chemicals, Inc.) as the X layer and ethylene-vinyl acetate copolymer (EVA, manufactured by Tosoh Corporation) as the Y layer, two materials three-layer (X layer / Y layer / X layer) extrusion T-die molding machine was used for molding. The extrusion temperature was implemented under the following conditions.

[0245] X layer: 200℃

[0246] Y layer: 200℃

[0247] X layer: 200℃

[0248] Die temperature: 200℃

[0249] The three-layer substrate of two materials PP / EVA / PP (thickness: PP / EVA / PP = 50 μm / 200 μm / 50 μm) is integrated by co-extrusion molding from a T-die, and after it is fully solidified, it is wound into a roll, thereby obtaining a substrate (3) as a wound body (total thickness = 300 μm).

[0250] [Manufacturing Example 4]: Manufacture of substrate (4)

[0251] Using polyethylene (ethylene-α-olefin copolymer type, PE, manufactured by Mitsui Chemicals, Inc.) as the X layer and polypropylene (propylene-1-butene-α-olefin copolymer type, PP, manufactured by Mitsui Chemicals, Inc.) as the Y layer, two materials three-layer (X layer / Y layer / X layer) extrusion T-die molding machine was used for molding. The extrusion temperature was implemented under the following conditions.

[0252] X layer: 200℃

[0253] Y layer: 200℃

[0254] X layer: 200℃

[0255] Die temperature: 200℃

[0256] The three-layer substrate layer of two materials PE / PP / PE (thickness: PE / PP / PE = 25 μm / 100 μm / 25 μm) is integrated by co-extrusion molding from a T-die, and after it is fully solidified, it is wound into a roll, thereby obtaining a substrate (4) as a wound body (total thickness = 150 μm).

[0257] [Manufacturing Example 5]: Manufacture of substrate (5)

[0258] Thermoplastic polyurethane (TPU, product name: Silklon NES85, manufactured by Okura Industries, Ltd., thickness = 100 μm) was used as the substrate (5).

[0259] [Manufacturing Example 6]: Manufacture of substrate (6)

[0260] Thermoplastic polyurethane (TPU, product name: Esmer URS ET-B#6, manufactured by Nippon Matai Co., Ltd., thickness = 60 μm) was used as the substrate (6).

[0261] [Manufacturing Example 7]: Manufacture of substrate (7)

[0262] A SEBS·EVA blended sheet (Ultrasen 635 (manufactured by Tosoh Corporation): Kraton G1657 (manufactured by Kraton Polymer Japan Ltd.) = 70:30, manufactured by Nitoms, thickness = 150 μm) was used as a substrate (7).

[0263] [Manufacturing Example 8]: Manufacture of substrate (8)

[0264] A polyurethane sheet (product name: STK20D, manufactured by Nippon Matai Co., Ltd., thickness = 190 μm) was used as a substrate (8).

[0265] [Manufacturing Example 9]: Manufacture of an adhesive layer (1) composed of an acrylic adhesive (1)

[0266] In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube, a reflux condenser and a dropping funnel, 95 parts of butyl acrylate (BA) as monomer components, 5 parts of acrylic acid (AA), 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator and ethyl acetate as a polymerization solvent were added, and solution polymerization was carried out at 60°C for 6 hours to obtain a solution of an acrylic polymer (AP1). The Mw of the acrylic polymer (AP1) was 60×10 4 .

[0267] To the obtained acrylic polymer (AP1) solution, 30 parts of a terpene phenol resin (YS Polyster S145 manufactured by Yasuhara Chemical Co., Ltd., softening point 145°C), 2 parts of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation), 0.01 parts of an epoxy crosslinking agent (TETRAD-C manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 30 parts of aluminum hydroxide particles (B103 manufactured by Nippon Light Metal Co., Ltd.) as filler particles were added and stirred and mixed to prepare an adhesive composition. The filler particles had an average particle size of 8 μm, the proportion of particles having a particle size of less than 25 μm was 85% or more, and the proportion of particles having a particle size of less than 1 μm was 3%.

[0268] Two release liners obtained by treating a 38 μm PET film with polysiloxane were prepared. The above-mentioned adhesive composition was applied to one side (release side) of each of these release liners so as to have a thickness of 50 μm after drying, and dried at 100° C. for 2 minutes. In this manner, adhesive layers (1) (first adhesive layer and second adhesive layer) composed of an acrylic adhesive (1) were formed on the release sides of the two release liners.

[0269] [Manufacturing Example 10]: Manufacture of an adhesive layer (2) composed of a rubber-based adhesive (1)

[0270] SIS block copolymer (product name "Quintac 3520", manufactured by Nippon Zeon Co., Ltd.): 100 parts, terpene phenol resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polyster S145", softening point 145°C): 20 parts, terpene phenol resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polyster T145", softening point 145°C): 20 parts, terpene resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Resin PX1150N", softening point 115°C): 30 parts, isocyanate crosslinking agent (manufactured by Tosoh Corporation, product name "Coronate L"): 0.75 parts, stabilizer (manufactured by BASF, product name "Irgafos 168"): 2 parts and antioxidant (manufactured by BASF, product name "Irganox 565")): 1 part, and dissolved in toluene, thereby preparing an adhesive composition.

[0271] Two release liners obtained by treating a 38 μm PET film with polysiloxane were prepared. The above-mentioned adhesive composition was applied to one side (release side) of each of these release liners so that the thickness after drying was 50 μm, and dried at 100° C. for 2 minutes. In this manner, adhesive layers (2) (first adhesive layer and second adhesive layer) composed of a rubber-based adhesive (1) were formed on the release sides of the two release liners.

[0272] [Manufacturing Example 11]: Manufacture of an adhesive layer (3) composed of an acrylic adhesive (1)

[0273] In the same manner as in Production Example 9, a pressure-sensitive adhesive composition was obtained.

[0274] Two release liners obtained by treating a 38 μm PET film with polysiloxane were prepared. The above-mentioned adhesive composition was applied to one side (release side) of each of these release liners so that the thickness after drying was 95 μm, and dried at 100° C. for 2 minutes. In this manner, adhesive layers (3) (first adhesive layer and second adhesive layer) composed of an acrylic adhesive (1) were formed on the release sides of the two release liners.

[0275] [Manufacturing Example 12]: Manufacture of an adhesive layer (4) composed of a rubber-based adhesive (2)

[0276] SBS block copolymer (product name "Kraton D1101JU", manufactured by Kraton Polymer Co., Ltd.): 100 parts, softener (product name "Komorex F22", manufactured by JXTG Energy Co., Ltd.): 3 parts, C5 petroleum resin (product name "Quintone U185", manufactured by Nippon Zeon Co., Ltd.): 80 parts, terpene resin (product name "Piccolyte A-115", manufactured by Harcules): 40 parts, terpene phenol resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polyster S145", softening point 145°C): 50 parts, isocyanate crosslinking agent (manufactured by Tosoh Corporation, product name "Coronate L"): 3 parts, anti-aging agent (product name "Nocrac 200", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.): 2 parts, anti-aging agent (product name "Nocrac MB", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.): 1 part, a stabilizer (manufactured by BASF, product name "Irgafos 168"): 2 parts, and an antioxidant (manufactured by BASF, product name "Irganox 565"): 1 part were dissolved in toluene to prepare a binder solution.

[0277] Two release liners obtained by treating a 38 μm PET film with polysiloxane were prepared. The above-mentioned adhesive composition was applied to one side (release side) of each of the release liners so that the thickness after drying was 50 μm, and dried at 100° C. for 2 minutes. In this manner, adhesive layers (4) (first adhesive layer and second adhesive layer) composed of a rubber-based adhesive (2) were formed on the release sides of the two release liners.

[0278] [Manufacturing Example 13] Manufacture of an adhesive layer (5) composed of a rubber adhesive (3): SEBS block copolymer (product name "Kraton G1657VS", manufactured by Kraton Polymer Co., Ltd.): 70 parts, SIS block polymer (product name "Quintac 3520", manufactured by Nippon Zeon Co., Ltd.): 30 parts, softener (product name "Diana Process Oil PW-90", manufactured by Idemitsu Kosan Co., Ltd.): 30 parts, alicyclic saturated hydrocarbon resin (product name "Arkon P100", manufactured by Arakawa Chemical Industries, Ltd.): 160 parts, polyethylene resin (product name "Sumikathene EMB-23", manufactured by Sumitomo Chemical Co., Ltd.): 5 parts, antioxidant (product name "Nocrac 200", manufactured by Ouchi Shinko Chemical Co., Ltd.): 2 parts, antioxidant (product name "Nocrac MB", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.): 1 part, stabilizer (manufactured by BASF, product name "Irgafos 168"): 2 parts, antioxidant (manufactured by BASF, product name "Irganox 565"): 1 part were kneaded to prepare an adhesive composition.

[0279] Two release liners obtained by treating a 38 μm PET film with polysiloxane were prepared. The adhesive composition was extruded onto one surface (release surface) of each of the release liners using an extruder at 200° C. so as to have a thickness of 50 μm. In this manner, adhesive layers (5) (first adhesive layer and second adhesive layer) composed of a rubber adhesive (3) were formed on the release surfaces of the two release liners.

[0280] [Manufacturing Example 14]: Manufacture of an adhesive layer (6) composed of an acrylic adhesive (2)

[0281] PSA layers (6) (first PSA layer and second PSA layer) each composed of an acrylic PSA (2) were formed on the release surfaces of two release liners in the same manner as in Production Example 9 except that no filler particles were used.

[0282] [Example 1]

[0283] The adhesive layer (1) formed on the release surface of the two release liners obtained in Manufacturing Example 9 was respectively attached to the two sides of the substrate (1) obtained in Manufacturing Example 1. The release liner remained on the adhesive layer (1) as it was, and was used to protect the surface of the adhesive layer (1). The obtained structure was passed through a laminator (0.3 MPa, speed 0.5 m / min) at 70°C once, and then aged in an oven at 50°C for 2 days. In this way, a double-sided adhesive tape (1) with a total thickness of 250 μm was produced. Various results are shown in Table 1.

[0284] [Example 2]

[0285] A double-sided pressure-sensitive adhesive tape (2) having a total thickness of 300 μm was prepared in the same manner as in Example 1 except that the substrate (2) obtained in Production Example 2 was used instead of the substrate (1).

[0286] [Example 3]

[0287] A double-sided adhesive tape (3) having a total thickness of 400 μm was prepared in the same manner as in Example 1 except that the substrate (3) obtained in Production Example 3 was used instead of the substrate (1).

[0288] [Example 4]

[0289] A double-sided pressure-sensitive adhesive tape (4) having a total thickness of 250 μm was prepared in the same manner as in Example 1 except that the substrate (4) obtained in Production Example 4 was used instead of the substrate (1).

[0290] [Example 5]

[0291] The adhesive layer (2) formed on the release surface of the two release liners obtained in Manufacturing Example 10 was respectively attached to the two sides of the substrate (4) obtained in Manufacturing Example 4. The release liner remained on the adhesive layer (2) as it was, and was used to protect the surface of the adhesive layer (2). The obtained structure was passed through a 70°C laminator (0.3MPa, speed 0.5m / min) once, and then aged in an oven at 50°C for 2 days. In this way, a double-sided adhesive tape (5) with a total thickness of 250μm was produced. Various results are shown in Table 1.

[0292] [Example 6]

[0293] A double-sided pressure-sensitive adhesive tape (6) having a total thickness of 200 μm was prepared in the same manner as in Example 1 except that the substrate (5) obtained in Production Example 5 was used instead of the substrate (1).

[0294] [Example 7]

[0295] A double-sided pressure-sensitive adhesive tape (7) having a total thickness of 200 μm was prepared in the same manner as in Example 5 except that the substrate (5) obtained in Production Example 5 was used instead of the substrate (4).

[0296] [Example 8]

[0297] The adhesive layer (3) formed on the release surface of the two release liners obtained in Manufacturing Example 11 was respectively attached to the two sides of the substrate (6) obtained in Manufacturing Example 6. The release liner remained on the adhesive layer (3) as it was, and was used to protect the surface of the adhesive layer (3). The obtained structure was passed through a laminator (0.3 MPa, speed 0.5 m / min) at 70°C once, and then aged in an oven at 50°C for 2 days. In this way, a double-sided adhesive tape (8) with a total thickness of 250 μm was produced. Various results are shown in Table 1.

[0298] [Example 9]

[0299] A double-sided pressure-sensitive adhesive tape (9) having a total thickness of 250 μm was prepared in the same manner as in Example 5 except that the substrate (7) obtained in Production Example 7 was used instead of the substrate (4).

[0300] [Example 10]

[0301] The adhesive layer (4) formed on the release surface of the two release liners obtained in Manufacturing Example 12 was respectively attached to the two sides of the substrate (7) obtained in Manufacturing Example 7. The release liner remained on the adhesive layer (4) as it was, and was used to protect the surface of the adhesive layer (4). The obtained structure was passed through a 70°C laminator (0.3MPa, speed 0.5m / min) once, and then aged in an oven at 50°C for 2 days. In this way, a double-sided adhesive tape (10) with a total thickness of 250μm was produced. Various results are shown in Table 1.

[0302] [Example 11]

[0303] The adhesive layer (5) formed on the release surface of the two release liners obtained in Manufacturing Example 13 was respectively attached to the two sides of the substrate (7) obtained in Manufacturing Example 7. The release liner remained on the adhesive layer (5) as it was, and was used to protect the surface of the adhesive layer (5). The obtained structure was passed through a 70°C laminator (0.3MPa, speed 0.5m / min) once, and then aged in an oven at 50°C for 2 days. In this way, a double-sided adhesive tape (11) with a total thickness of 250μm was produced. Various results are shown in Table 1.

[0304] [Example 12]

[0305] The adhesive layer (2) formed on the release surface of the two release liners obtained in Manufacturing Example 10 was respectively attached to the two sides of the substrate (7) obtained in Manufacturing Example 7. The release liner remained on the adhesive layer (2) as it was, and was used to protect the surface of the adhesive layer (2). The obtained structure was passed through a 70°C laminator (0.3MPa, speed 0.5m / min) once, and then aged in an oven at 50°C for 2 days. In this way, a double-sided adhesive tape (12) with a total thickness of 250μm was produced. Various results are shown in Table 1.

[0306] [Comparative Example 1]

[0307] A double-sided pressure-sensitive adhesive tape (C1) having a total thickness of 250 μm was prepared in the same manner as in Example 1 except that the substrate (8) obtained in Production Example 8 was used instead of the substrate (1).

[0308] [Comparative Example 2]

[0309] The adhesive layers (6) formed on the release surfaces of the two release liners obtained in Manufacturing Example 14 were respectively attached to the two surfaces of the substrate (1) obtained in Manufacturing Example 1. The release liners remained on the adhesive layer (6) as they were, and were used to protect the surface of the adhesive layer (6). The obtained structure was passed through a laminator (0.3 MPa, speed 0.5 m / min) at 70° C. once, and then aged in an oven at 50° C. for 2 days. In this way, a double-sided adhesive tape (C2) with a total thickness of 250 μm was produced.

[0310] Table 1 shows various results.

[0311]

[0312]

[0313] Industrial Applicability

[0314] The double-sided pressure-sensitive adhesive tape in the embodiment of the present invention is used, for example, to fix or temporarily fix parts of electronic devices, typically mobile devices such as mobile phones, smartphones, and tablet terminals.

[0315] Reference numerals

[0316] 10 Base material layer (A)

[0317] 21 Adhesive layer (B1)

[0318] 22 Adhesive layer (B2)

[0319] 200 Double-sided adhesive tape

Claims

1. A double-sided adhesive tape, comprising an adhesive layer (B1), a substrate layer (A), and an adhesive layer (B2) in this order, wherein: The adhesive layer (B1) and the adhesive layer (B2) each contain at least one selected from the group consisting of an acrylic adhesive and a rubber adhesive, and the acrylic adhesive contains a filler, The adhesive layer (B1) and the adhesive layer (B2) each have an initial adhesive force of 8 N / 10 mm or more, the initial adhesive force being the initial adhesive force to a SUS plate under the conditions of 23° C., 50% RH, a peeling angle of 180 degrees, and a peeling speed of 300 mm / min as specified in JIS-Z-0237-2000, and The elongation at break of the double-sided adhesive tape measured by the "elongation" measurement method specified in JIS-K-7311-1995 is 600% or more, The substrate layer (A) is a three-layer substrate layer of two materials with a structure of X layer / Y layer / X layer, The two-material three-layer type substrate layer is a two-material three-layer type substrate layer having a layer structure of polypropylene / ethylene-vinyl acetate copolymer / polypropylene or a two-material three-layer type substrate layer having a layer structure of polyethylene / polypropylene / polyethylene.

2. The double-sided adhesive tape according to claim 1, wherein The tensile strength of the double-sided adhesive tape when elongated by 600%, measured by the “elongation” measurement method specified in JIS-K-7311-1995, is 12 N / 10 mm or more.

3. The double-sided adhesive tape according to claim 1 or 2, wherein: The total thickness of the double-sided adhesive tape is 100 μm to 700 μm.

4. The double-sided adhesive tape according to claim 1 or 2, wherein The thickness of the substrate layer (A) is 20 μm to 500 μm.

5. The double-sided adhesive tape according to claim 1 or 2, wherein The thickness of the adhesive layer (B1) and the adhesive layer (B2) is each 10 μm to 200 μm.

6. The double-sided adhesive tape according to claim 1 or 2, wherein: The double-sided adhesive tape is used for electronic equipment.

Citation Information

Patent Citations

  • Double-sided pressure-sensitive adhesive sheet

    JP2013119564A

  • Double-sided adhesive tape for drawing release and electronic apparatus

    JP2016008288A

  • Adhesive sheet for portable electronic device

    JP2016029155A

  • Pressure sensitive adhesive sheet

    JP2017197689A

  • Double-sided adhesive tape

    JP2019006908A